Consultations in the emergency department: a systematic review of the literature. Issue 1 (21st December 2007) - Lee, Rene S; Woods, Rob; Bullard, Michael; Holroyd, Brian R; Rowe, Brian H
Abstract : Objectives: Consultation is a common and important aspect of emergency department (ED) practice which can lead to delays in patient flow. Little is known about ED consultations and this review systematically evaluated the literature on ED consultations. Methods: Comprehensive searches of MEDLINE, PUBMED, SCIRUS, Cochrane Library, Web of Science, Health Star and other databases from 1966 to 2007 were performed. The grey literature and reference lists were searched and authors were contacted to identify other eligible studies. Published and unpublished studies reporting the proportion of consultations in the ED using any type of design were considered for this review. Eligible studies were required to involve patients presenting to the ED. Studies reporting on the proportion of consultation in a specific subpopulation of patients and interventions to improve consultations were also considered for inclusion. Two reviewers independently selected studies and extracted data from included studies regarding the proportion of consultations in the ED or the patient subgroup. Individual study proportions were calculated together with 95% confidence intervals (CI). Results: From more than 15 000 pre-screened citations, 12 studies were finally included in the review. All but three of the included studies were published. Overall, four studies examined ED consultation proportions, six identified the rate of consultation for special populations of ED presentations and two examined interventions to improve consultations. Consultation varied from 20% to 40% for all patients, with lower proportions in the selected populations studied and a high rate of hospitalisation for consulted patients. Limited research on interventions to improve the ED consultation process has also been completed. Conclusions: Consultation research in the emergency setting is limited and variable; however, high consultation rates exist in some centres. This systematic review outlines the current state of the literature and suggests that further research is urgently needed.